The birth beliefs scale - a new measure to assess basic beliefs about birth - Heidi Preis; Yael Benyamini (Taylor & Francis Group, 2017)
Introduction: Basic beliefs about birth as a natural and safe or a medical and risky process are central in the decisions on where and how to birth. Despite their importance, they have not been studied separately from other childbirth-related constructs. Our aim was to develop a measure to assess these beliefs. Method: Pregnant Israeli women (N = 850, gestational week ≥14) were recruited in women's health centers, in online natural birth forums, and through home midwives. Participants filled in questionnaires including sociodemographic and obstetric background, the Birth Beliefs Scale (BBS), dispositional desire for control (DC) and planned mode of delivery. Results: Factor analyses revealed that the BBS is composed of two factors: beliefs about birth as a natural process and beliefs about birth as a medical process. Both subscales showed good internal and test-retest reliability. They had good construct validity, predicted birth choices, and were weakly correlated with DC. Women's medical obstetric history was associated with the BBS, further supporting the validity of the scale. Discussion: Beliefs about birth may be the building blocks that make up perceptions of birth and drive women's preferences. The new scale provides an easy way to distinctly assess them so they can be used to further understand planned birth behaviors. Additional studies are needed to comprehend how these beliefs form in different cultural contexts and how they evolve over time.